Antioxidative and photoprotective effects of pleurotus flabellatus (pink oyster mushroom) polysaccharides against UVA radiation-induced cytotoxicity in human dermal fibroblast (HS-27) cell line - Abdul Rahman, Norintan Suhaida; Hassan, Masriana; Hamid, Nur Izyanni; Mohamad, Shaiful Azuar; Mohamad, Najwa; Mahadi, Mahani; Zailan, Nur Fatin Zalikha; Ismail, Rozila (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: Ultraviolet (UV) A is the longest wavelength of UV radiation, accounts for approximately 95% of the radiation reaching the earth's surface. It can penetrate deeply into the skin layer and able to induce photoaging and photocarcinogenesis through the activation of reactive oxygen species (ROS). Polysaccharides-containing Pleurotus flabellatus (known as a pink oyster mushroom) has antioxidative properties and may inhibit free radical activities generated from UV radiation. Hence, this present study was to evaluate the antioxidative and photoprotective properties of exopolysaccharides (ExPFE) and exopolysaccharides (EnPFE) of Pleurotus flabellatus extracts on UVA irradiated human dermal fibroblast (HS-27) cell line. Methods: The antioxidant level of ExPFE and EnPFE was determined using 1,1-Diphenyl-2-picrylhydrazyl (DPPH) scavenging assay, while both cytotoxicity and photoprotective effects of the extracts on the HS-27 cell line were determined using CellTiter-Blue® cell viability assay. The effects of ExPFE and EnPFE on the HS-27 cell migration was evaluated using the scratch assay. Results: Both ExPFE and EnPFE exhibited respectable antioxidant and scavenging activity in DPPH. The extracts also demonstrated a non-cytotoxicity, but photoprotective effects to the HS-27 cells by increasing the percentage of cell viability and enhancing cell migration activity upon UVA exposure. Conclusion: The ExPFE and EnPFE exhibit antioxidative and photoprotective effects on UVA irradiated HS-27 cell line. This study suggests that pink oyster polysaccharides could be a potential natural bioactive compound for skin protection against UVA radiation.